Contextualizing entrepreneurial leadership in the K-12 school setting—lessons from Austria and Germany - Frentz, Jürgen; Frenz, Florian; Pashiardis, Petros; Brauckmann-Sajkiewicz, Stefan (Frontiers in Education, 2025)
Global megatrends such as climate change, demographic shifts, and technological disruption increasingly compel K-12 school leaders to innovate within complex and uncertain environments. Entrepreneurial School Leadership (ESL), encompassing opportunity recognition, initiative, and strategic resource management in a bureaucratic setting, offers a framework for adaptive and future-oriented K-12 leadership. This conceptual paper examines ESL in German-speaking countries, where educational traditions that prioritize humanistic Bildung over market-oriented models, interact with pressures for efficiency and accountability. A document analysis of normative school leadership profiles from Austria and Germany highlights the formal integration of entrepreneurial content knowledge and competencies, including innovation, networking, and strategic planning, while revealing persistent tensions between pedagogical and economic rationalities. The analysis underscores that ESL operates at the intersection of individual dispositions, institutional conditions, and national-cultural contexts. Future research should investigate how ESL is enacted in practice, including its potential for fostering social value, transformative innovation, and sustainable school development, while critically attending to unintended consequences and context-specific constraints.